Island Identification at River Estuary Based on Toponymy (Case Study: River Estuary of Bulungan, BulunganRegency, North Kalimantan Province) - Yulius Yulius; Ifan Ridho Suhelmi; M Ramdhan (Universitas Muhammadiyah Surakarta, 2014)
Toponymy is the scientific study of geographical names. Island Toponym represents step of island identi- fication by identifying its name and geographic position. Island Identification in toponymy was conducted through desk study and field survey. Desk study was implemented to obtain earlier description of islands physical condition, social and culture of local people. Field survey to obtain names of the islands was carried out by interviewing local people and positions were measured by using a simple GPS system then validated using nautical chart Dishidros publications 1997 and Image from Google Earth in 2013. The Survey at Bulungan Regency of East Kalimantan Province, 19 islands had been identified 7 islands which have not been listed at DEPDAGRI (Ministry of Internal Affairs) in 2004 but the other 10 islands have been named, and 9 island which is not drawn yet in sea chart published by DISHIDROS TNI-AL.